KOMUNIKASI ANTAR KELUARGA MUSLIM BEDA BUDAYA DI PALANGKA RAYA - Ngalimun Ngalimun; Rahmawati Rahmawati (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2020)
This study aims to  determine the  model of communication between Muslim families of different cultures and inhibiting factors of communication. This research was conducted on couples of five families who married with different cultures in the Tanjung Pinang sub-district, Pahandut sub-district, Palangka Raya City. With the marriage of different cultures is expected to enrich the culture and can also be used as lessons  for  individuals  who  want  to  do  the  marriage.  This  type  of  research  is descriptive  qualitative,  the  sample  of  this  study  is  5  families.  The  communication model of 5 Muslim families with different cultures can be seen from the adaptation process that occurs in their respective families. In adapting there are various things that start from the adaptation of the language, through habits, through different food tastes and complement each other so that each family has a different communication model. Whereas the factors which hamper communication in the family are the difficulty of language adjustment, the existence of prejudice, the communication that occurs is one- way or there is no feedback and errors in the evaluation of the message delivered.